PENGARUH PEMBERIAN Beauveria bassiana Vuill TERHADAP KEMATIAN DAN PERKEMBANGAN LARVA Spodoptera litura Fabricus DI RUMAH KACA - Raden M. Saleh, Rosdah Thalib dan Suprap . (Universitas Lampung, 2001)
The effects of beauveria bassiana vuill apllication upon the mortality and development of spodoptera litura fabricus larvae in glasshouse. A research has been done in order to know the effects of Beauveria bassiana Vuill application on the Spodoptera litura Fabricus larvae. The research was conducted in glasshouse of Jurusan Hama dan Penyakit Tumbuhan, Fakultas Pertanian Universitas Sriwijaya, by using completed randomized design with four Beauveria concentration as treatment and six replications. The treatments were 0, 104, 106 an d 108 Beauveria spores per cc of water. Each replication consists of four units of plant sample. The result of the study shows that 108 spores of Beauveria caused 70% larval mortality, the highest among all concentrations. The growth of the larval weight was decreeasing following the increasing of the Beauveria concentration. The changing in the body color and reducing in eating activities were showed by the larvae as the effects of Baeuveria apllication.